LEADERSHIP STYLE THROUGH A COLLABORATIVE AND PARTICIPATORY APPROACH IN STRENGTHENING ORGANIZATIONAL PERFORMANCE AND SUSTAINABLE DEVELOPMENT (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Leadership style is one of the most strategic factors influencing organizational effectiveness, employee motivation, innovative behavior, and institutional sustainability. In modern organizations, leadership is no longer limited to authority and control but extends to the ability to inspire, motivate, collaborate, and manage organizational transformation effectively. This article examines leadership style through a collaborative and participatory approach in strengthening organizational performance and supporting sustainable development. The study adopts a qualitative descriptive method using literature review and conceptual analysis. The discussion focuses on transformational, authentic, adaptive, and strategic leadership within the context of organizational transformation, public sector management, and sustainable organizational development. The findings indicate that collaborative and participatory leadership strengthens communication, teamwork, employee engagement, organizational learning, and innovation capability. Leadership styles that emphasize participation, trust, and empowerment significantly improve employee performance and organizational adaptability. Furthermore, collaborative leadership contributes to sustainable development by supporting organizational resilience, inclusive governance, innovation, and strategic partnerships. The study concludes that transformational, authentic, and strategic leadership styles are highly relevant for modern organizations, particularly in the public and health sectors, because they strengthen organizational competitiveness and long-term sustainability.